2009
DOI: 10.1002/ajpa.21098
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the gastrointestinal parasites of Colobus vellerosus at Boabeng‐Fiema, Ghana: Possible anthropozoonotic transmission

Abstract: Parasite richness and prevalence in wild animals can be used as indicators of population and ecosystem health. In this study, the gastrointestinal parasites of ursine colobus monkeys (Colobus vellerosus) at the Boabeng-Fiema Monkey Sanctuary (BFMS), Ghana, were investigated. BFMS is a sacred grove where monkeys and humans have long lived in relatively peaceful proximity. Fecal samples (n = 109) were collected opportunistically from >27 adult and subadult males in six bisexual groups and one all-male band from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 82 publications
6
29
0
Order By: Relevance
“…Despite intensive research, there are only a few reports with lower prevalence of Blastocystis sp. in wild chimpanzees and vervets (Ashford et al 2000;Legesse and Erko 2004;Muehlenbein 2005;Reynolds 2005), and there is only one report in captive guerezas (Teichroeb et al 2009). Recent surveys showed that Blastocystis sp.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Despite intensive research, there are only a few reports with lower prevalence of Blastocystis sp. in wild chimpanzees and vervets (Ashford et al 2000;Legesse and Erko 2004;Muehlenbein 2005;Reynolds 2005), and there is only one report in captive guerezas (Teichroeb et al 2009). Recent surveys showed that Blastocystis sp.…”
Section: Discussionmentioning
confidence: 93%
“…can be easily overlooked in fecal debris because of their small size, and thus the scarcity of reports in wild populations could be a result of methods used for detection (Stensvold et al 2007;Teichroeb et al 2009). From 13 morphologically identical subtypes of Blastocystis sp., 7 subtypes have been isolated from nonhuman primates; 5 of these subtypes occur in humans (Parkar et al 2010;Stensvold et al 2007Stensvold et al , 2009Teichroeb et al 2009;Yoshikawa et al 2004Yoshikawa et al , 2009. Some subtypes of Blastocystis sp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, the relationship between social status and measures of infection varies among studies, based on factors that are not yet fully understood. High rank has been associated with greater nematode egg output in male yellow baboons (P. cynocephalus; Hausfater and Watson, 1976), male gorillas (Gorilla beringei; Rothman et al, 2008), male ursine colobus (Teichroeb et al, 2009), and female Japanese macaques (MacIntosh et al, 2012). In contrast, studies on male red-fronted lemurs, male and female olive baboons, and female yellow baboons found no effect of rank on any measure of helminth infection (Hausfater and Watson, 1976;M€ uller-Graf et al, 1996;Clough et al, 2010).…”
Section: Alternative Causes Of Variability In Infection Patternsmentioning
confidence: 99%
“…Although the emphasis of these studies has been on the dog as a reservoir of human infection, some recent reports investigating the molecular epidemiology of infections with species of Giardia in wild primates have provided further evidence of zoonotic transmission in localised foci, and have also demonstrated that 'reverse zoonotic transmission' (zooanthroponotic) is an important factor that must be considered in understanding the epidemiology of infections with these parasites [115,116,117].…”
Section: Echinococcus Giardia and Cryptosporidiummentioning
confidence: 99%